Mother Teresa - Demi (Margaret K. McElderry Books, 2005)
A biography of Agnes Gonxha Bojaxhiu, known as Mother Teresa, who spent most of her life serving "the poorest of the poor" in Calcutta, India. It is not how much we do but how much love we put in the doing that makes our offering something beautiful for God. -- MOTHER TERESA Born Agnes Gonxha Bojaxhiu in 1910, Mother Teresa was called to a religious life at a young age and began her novitiate in 1928. She took the name "Teresa" after Saint Teresa of Lisieux, the patroness of missionaries, and dedicated her entire life to helping the poorest of the poor in India and, later, throughout the world. Founder of the Missionaries of Charity in 1950, she came to be known as Mother Teresa and oversaw thousands of nuns as they ministered to the poor, the starving, and the dying. Mother Teresa was the recipient of many of the world's most prestigious humanitarian awards, including the United States Medal of Honor and the Nobel Peace Prize. She died in Calcutta, India, in 1997 and was beatified by Pope John Paul II on October 19, 2003.